2021
DOI: 10.1016/j.jcot.2020.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative tendon retraction, not smoking, is a risk factor for failure with continuity after rotator cuff repair

Abstract: Background: Smoking is a poor prognostic factor for healing after rotator cuff repair and is associated with inferior results. We hypothesized that smokers would have higher recurrent tear rates and more postoperative myotendinous junction (MTJ) retraction in healed repairs than nonsmokers three months postoperatively. Methods: Rotator cuff repairs (RCRs) were retrospectively reviewed over a 2-year period. Patients underwent magnetic resonance imaging (MRI) within 6 months prior to surgery and again at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…6 Preoperative tear size and retraction are the main reported risk factors for poorer clinical outcomes and retear rates. 7 Not surprisingly, shoulder surgeons have explored whether augmentation of cuff repair would not only result in better cuff integrity but also reduce retear rates. 5,[8][9][10] An earlier study by Barber et al has been promising reporting intact repairs in 85% compared with 40% in nonaugmented repairs at a mean follow-up of two years.…”
Section: See Related Article On Page 38mentioning
confidence: 99%
“…6 Preoperative tear size and retraction are the main reported risk factors for poorer clinical outcomes and retear rates. 7 Not surprisingly, shoulder surgeons have explored whether augmentation of cuff repair would not only result in better cuff integrity but also reduce retear rates. 5,[8][9][10] An earlier study by Barber et al has been promising reporting intact repairs in 85% compared with 40% in nonaugmented repairs at a mean follow-up of two years.…”
Section: See Related Article On Page 38mentioning
confidence: 99%
“…Previous study has demonstrated that retracted tears are a risk factor for retears with continuity. 36 The myotendinous junction retracts in these retears with continuity, which would obviously influence pennation angle and cross-sectional area measures.…”
mentioning
confidence: 99%